Fostering And Developing Islamic Boarding School (Pesantren) Literature In East Java - Furoidatul Husniah; Mintowati Mintowati; Anas Ahmadi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Islamic Boarding School (Pesantren) literature becomes an increasingly interesting discourse in literary events in Indonesia. The fostering and developing Pesantren literature in East Java has been done as an effort to revitalize Pesantren literature. The research method used was qualitative with data in the form of activities, documents that indicated as an effort to foster language, and the development of Pesantren literature, especially in East Java. The data were collected through documentation and then analyzed by reading, classifying, analyzing, and interpreting efforts that have been documented in the context of fostering and developing Islamic boarding school (Pesantren) literature. The results of this paper showed the great number of pesantren students’ (santri) works that have been published by well-known publishers in Indonesia, the relationship of santri who were members of the community as well as halaqoh, and also fostering santri in Pesantren to express themselves in writing literature work. Meanwhile, efforts to develop Pesantren literature led to its literary themes that extended to social and national themes, the transfer of novels to films, and also the existence of a synergy of actors (Minister of Religion, Kyai, students (santri), Language Agency of East Java) to plan Pesantren literature towards change by exploring nationalism and building nationality.